2015
DOI: 10.1038/bjc.2015.206
|View full text |Cite
|
Sign up to set email alerts
|

miR-30e* is an independent subtype-specific prognostic marker in breast cancer

Abstract: Background:Breast cancer clinical outcome is affected by tumor molecular features, and the identification of subtype-specific prognostic biomarkers is relevant for breast cancer translational research. Gene expression signatures proved to be able to complement prognostic information provided by classical clinico-pathological features. Recently, microRNAs (miRNAs) have been causally linked to tumorigenesis and cancer progression and have been associated with patient outcome, also in breast cancer.Methods:MicroR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 61 publications
2
45
0
Order By: Relevance
“…By contrast, we have just begun to elicit the role of miR-30e-5p in tumour development. Tissue microarray analysis suggests that high levels of miR-30e-5p in primary tumours are associated with a favourable prognosis in breast cancer [60]. In our study, we observed increased levels of miR-181a-5p and miR-30e-5p in breast cancer biopsies as compared to normal mammary gland tissue.…”
Section: Discussionsupporting
confidence: 64%
“…By contrast, we have just begun to elicit the role of miR-30e-5p in tumour development. Tissue microarray analysis suggests that high levels of miR-30e-5p in primary tumours are associated with a favourable prognosis in breast cancer [60]. In our study, we observed increased levels of miR-181a-5p and miR-30e-5p in breast cancer biopsies as compared to normal mammary gland tissue.…”
Section: Discussionsupporting
confidence: 64%
“…Expression levels of a number of miRNAs, which are either positively or inversely associated with metastatic status, disease-free time and overall survival of breast cancer patients have been identified [225][226][227][228][229][230][231][232][233][234][235][236][237][238][239][240] and are detailed in Table 3. The most relevant miRNA with prognostic value in breast cancer is miR-210, the aforementioned oncogenic miRNA implicated in the DCIS-to-IDC transition.…”
Section: Translational Implications Of Ncrnas In Breast Cancermentioning
confidence: 99%
“…tissue miR-30 e* miR-30 e* was identified as independent protective prognostic factor in lymph node-negative untreated patients with ESR1þ/ERBB2-tumors [240] miRNA-based oligonucleotides to increase their in vivo stability and binding affinity to endogenous RNA targets. Given that naked nucleic acid molecules are not generally suitable for in vivo applications owing to their intrinsic negative charge, packaging of the gene silencing agents (e.g.…”
Section: Ncrnas As Therapeutic Targetsmentioning
confidence: 99%
“…Accumulating evidence demonstrated that miRNAs show distinct expression signatures across different cancer subtypes, and have either oncogenic or tumor-suppressive roles [17, 18]. Our previous study discovered that miR-199a-5p showed low expression in TNBC patients’ circulation when compared with other subtypes of breast cancers, also the expression level was linked with disease stage, and suggested to be a potential biomarker for TNBC [19].…”
Section: Introductionmentioning
confidence: 99%